A thermal performance evaluation of a new integrated gas turbine-based multigeneration plant with hydrogen and ammonia production. (18th August 2021) - Tukenmez, Nejat; Yilmaz, Fatih; Ozturk, Murat
Abstract: In this study, a new combined system driving a gas turbine cycle has been proposed for seven useful outputs of power, hydrogen, ammonia, heating-cooling, drying and hot water. The proposed integrated plant mainly consists of the gas turbine cycle, Rankine cycle, two organic Rankine cycles, ejector-based cooling, hydrogen production and liquefaction, ammonia production and storage, drying and hot water generation sub-systems. In order to demonstrate that the designed system is an efficient and environmentally plant, the performance analysis was performed by using a software package. Before performing the performance assessment of the plant, the mathematical model of the integrated plant is prepared in accordance with thermodynamic equations. Basic equilibrium equations are used for the thermodynamic equations used. Obtaining multiple useful outputs from the system also have the positive effect on the system effectiveness. The energetic effectiveness of integrated plant for multigeneration with hydrogen and ammonia production is computed to be 62.18% and exergetic efficiency is 58.37%. In addition, the energetic and exergetic effectiveness of hydrogen production and liquefaction process are 57.92% and 54.23%, respectively. Highlights: A novel multigeneration plant with hydrogen and ammonia production is proposed. Effect of design indicators on performance and CO2 emission of plant are analyzed. Energy and exergy efficiencies of whole system and sub-systems are evaluated. Environmental analysis of combined plant-based CO2 emission is investigated.